Population structure and growth of two opulations of Aegla Schmitti Hobbs III, 1979 (Anomura, Aeglidae) in the eastern Paraná state, Brazil - Trevisan, André; Marochi, Murilo Z. [UNESP]; Masunari, Setuko (Academia Brasileira de Ciências, 2021)
The population structure and growth of two populations (Arraial and Capivari rivers) of Aegla schmitti was evaluated. The following parameters were determined: size, age structure, sex ratio, recruitment period, and sampling method selectivity (traps and handnet). There was variation between males and females. The carapace length size class distribution was unimodal in the Arraial River, and polymodal in the Capivari River. The sampling method influenced the proportion of demographic categories. The recruitment occurred mostly between October and December. The growth curves for the Arraial and Capivari rivers, respectively, were Ct= 26,50[1- e -0,004(t+53,36)] and Ct= 34,79[1- e -0,0024(t+122,34)] for males, and Ct= 23,07[1- e -0.0027(t+23,18)] and Ct= 25.52[1- e -0,0033(t+19,51)] for females. The maximum CL estimated for males and females were 26.50 and 23.07mm for the Arraial River, and 34.79 and 25.52mm for the Capivari River. Longevity was estimated in 2 years for females of both populations, and 2.5 and 3 years for males of the Arraial and Capivari rivers, respectively. The results allow for the characterization of the growth patterns of A. schmitti in two hydrographic basins, providing information for the species’ preservation and also demonstrating the selectivity of the different sampling methods used for aeglids.
Keywords: Population growth; recruitment; sex ratio; size composition; von Bertalanffy model